Check cystoscopy in the management of anterior urethral valves in a cohort of pediatric patients. Issue 2 (April 2021) - Cini, Chiara; Mantovani, Alberto; Cianci, Maria Chiara; Landi, Luca; Bortot, Giulia; Sforza, Simone; Taverna, Maria; Elia, Antonio; Masieri, Lorenzo
Summary: Introduction: Anterior urethral valves (AUV) are a rare cause of lower urinary tract obstruction which could progress to renal damage, Clinical presentation varies according with patient's age and severity of obstruction, but, in most cases, diagnosis is based on voiding cysto-urethrogram (VCUG). To date, the treatment of choice is endoscopic ablation even if approved guidelines about the overall management of AUVs, including the recognition and treatment of residual valves, are not available. Objective: We describe our protocol for AUV treatment based on primary endoscopic valve ablation followed by check cystoscopy 15 days later. Study design: Medical records of 5 patients with AUVs admitted from 2008 to 2018 to our Pediatric Urology Unit were retrospectively reviewed. Blood tests, urinalysis, renal US and VCUG were performed in all children, while urodynamic evaluation was performed in the 3/5 patients who could void spontaneously. All patients underwent endoscopic valves ablation and after 15 days after a second look cystoscopy was performed. Follow up was based on clinical and radiological evaluation with US, urinalysis and blood tests. Postoperative non-invasive urodynamic studies were performed in the 3/5 patient toilet-trained patients and VCUG was performed in 1/5 patient. Results: and Discussion: At primary endoscopic ablation cystoscopy revealed AUVs in the penile urethra in three patients, in the penoscrotal urethra in one case, in the bulbar urethra in another case. In 3/5 patients check cystoscopy found residual valves and a second endoscopic ablation was performed. All patients achieved symptoms release and improved urodynamic parameters. No intra or post-operative complication were reported. The assessment of residual valves is variable in literature and it is usually described for posterior urethral valves (PUVs). Few series report the use of VCUG within the first week after valve ablation, our experience instead suggests that performing a second look cystoscopy, is very effective to evaluate the presence of residual AUVs and eventually proceed with further ablation. Conclusion: Endoscopic ablation is the gold standard treatment for AUV, but residual valves management is not clearly defined. According to our experience, a check cystoscopy 15 days after primary ablation allows to identify and treat possible residual valves showing good results in terms of safety and efficacy.